Pendidikan Politik Pada Pondok Pesantren Abu Manshur Kabupaten Cirebon - Nurul Azizatul Isnaini; Rasmuin Rasmuin (Jurnal Al-Manar, 2022)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia that have contributed greatly to the development of social and political religions. Pesantren is a replica of life that combines various life skills, including political skills. This research was conducted using qualitative methods. Data obtained through observation, interviews and documentation. The results showed that in imparting political education to its students, the Abu Manshur Islamic Boarding School did so in two ways, namely theoretically and practically. Theoretically, this is done by incorporating political education into various routine activities of Islamic boarding schools. Meanwhile, practically, political education for santri is carried out through intensive leadership training and through field practice activities to other institutions.